Strategi Penguatan Moderasi Beragama Melalui Kegiatan Festival Anak Sholeh di Desa Perkebunan Tanjung Beringin - Sinaga, Husnia Amro Br; Syari, Isma Aulia Zamaakh; Anggraini, Arizka; Pane, Mahfuzha; Ong, Aldi Maulana; Al Rizky, Muhammad Furqan; Husein, Ismail (CV. Rayyan Dwi Bharata, 2024)
Religious moderation is the most important key in maintaining harmony and harmony in a diverse society to prevent radicalism. Religious moderation and tolerance are two different and different things. Religious moderation is a path that consists of several stages that must be passed, while tolerance is the result of the stages that have been passed before. From religious moderation, an attitude of tolerance will be formed between fellow human beings, so that harmony between religious communities will be created which will later function to strengthen the unity and unity of the Indonesia nation. Humans are required to interact to meet their needs in society. Relations between religious people are based on the principle of good brotherhood, working together to face enemies and defending those who suffer. Religious harmony is needed in establishing good relationships in community life. In this context, it is discussed that this research is an inculcation of the value of tolerance between religious communities.